A designed bi-functional sugar-based surfactant: micellar catalysis for C–X coupling reaction in water. Issue 10 (2nd May 2019) - Ge, Xin; Zhang, Shihui; Chen, Xinzhi; Liu, Xuemin; Qian, Chao
Abstract : A bi-functional sugar-based surfactant ALA14 was designed as the ligand and micelle constructor and demonstrated to promote the copper-catalyzed C–X coupling reaction in water. Abstract : A bi-functional sugar-based surfactant ALA14 was designed as the ligand and micelle constructor and demonstrated to promote the copper-catalyzed C–X coupling reaction in water. The nature of this micelle, formed by sugar-based surfactants, was investigated with CMC, DLS, and TEM, by which encapsulation and aggregation of the substrates in micelles were verified. Additionally, it was addressed by 1 H-NMR analysis that the enrichment position of the substrates is in the lipophilic alkyl chain. Finally, moderate to excellent yields of the aimed products were obtained in this work. This remarkably simple strategy expanded the scope of C–X coupling reaction in water; most notably, both water and ALA14 can be recycled and reused.